Studi Preferensi Pemilihan Merek Dekanter 3 Fasa pada Pabrik Kelapa Sawit menggunakan Analytic Hierarcy Process - Muhammad Ansori Nasution; Meta Rivani; Arjanggi Nasution; Rizki Amalia; Ayu Wulandari; Rizalmi Fitrah; Yahdi Akbar (Pusat Penelitian Kelapa Sawit, 2021)
Decanter is used to separate oil phase from underflow sludge of continuous settling tank (CST) in Palm Oil Mills (POM). The most commonly type of decanter is 3-phase decanter. This paper describes the brand preferences in 3-phase decanter selection by using the Analytical Hierarchy Process (AHP) method. Before the AHP was done, expert correspondent prepared a list of criteria and sub-criteria for 3-phase decanter brand selection. AHP was conducted in 3 steps, which were: i) criteria classification, ii) pair-wise comparison of criteria and sub-criteria, that did by user correspondent, and iii) evaluation on the 3-phase decanter selection based on the brand comparison, that did by user correspondent. AHP simulation was carried out using Expertchoice® version 11. The first step of AHP generated: i) a question list arranged in questionnaire form, regarding criteria and sub-criteria concerning the brand of the decanter, and ii) weight value for each question. The second step of AHP revealed that technical criteria are preferable to economic than technical criteria. The spare part availability has the highest preference value amongst the economic sub-criteria, while oil losses has the highest preference in the technical sub-criteria. The third step of AHP showed that the decanter of Brand B is on the top ranking, with an economic and a technical preference value of 0.148 and 0.130, respectively. These results indicated that preference values can change if a complex analysis of criteria, sub-criteria, and decanter brands is involved in the one system analysis. Results of sensitivity analysis shows that both the decanter of Brand B and Brand E get the first rank in preference, which Brand E is on third rank before the sensitivity analysis is deducted.